Thyrotropin levels in first-episode bipolar disorder and their association with clinical phenotypes: systematic review and meta-analysis - Elisa Gatta; Elisa Gatta; Virginia Maltese; Francesco Dondi; Pietro Bellini; Massimiliano Ugoccioni; Irene Silvestrini; Anna Ceraso; Anna Ceraso; Antonio Vita; Antonio Vita; Mario Rotondi; et al. (Frontiers in Endocrinology)
IntroductionThyroid hormones play a crucial role in brain function, yet the relationship between TSH and bipolar disorder remains unclear. This review aims to synthesize the current literature to clarify the interplay between serum TSH levels and both the phenotype and severity of bipolar disorder.MethodsA comprehensive literature search was conducted across PubMed/MEDLINE, Scopus, and Web of Science databases through May 2025. Studies were included based on the PICO framework: What are the TSH levels in first-episode drug-naïve BD patients compared to healthy controls, and do TSH levels differ between manic and depressive phenotypes? The review follows PRISMA guidelines. Study quality and risk of bias were assessed using QUADAS-2.ResultsSeventeen studies out of 3,007 were included. Meta-analysis revealed that 1,946 drug-naïve BD patients had lower TSH levels compared to 400 healthy controls (SMD = -0.395 mIU/L, 95% CI: -0.695 to -0.095). Among 830 BD patients, those with a depressive phenotype (n=494) had higher TSH levels than manic patients (SMD = +0.575 mIU/L, 95% CI: -1.074 to -0.075).DiscussionOur data suggest that TSH levels can modulate the onset and severity of psychiatric diseases. Interventional studies targeting TSH modulation, particularly in euthyroid patients, are warranted.